ANALISIS TINDAK TUTUR ABU UBAIDAH DALAM PIDATO 36 HARI PASCA PERANG HAMAS-ISRAEL: TEORI JOHN SEARLE - Uswah Mujahidah Rasuna Said; Muhammad Jaohar Tsani; Asep Sopian (Universitas Islam Negeri Mataram, 2024)
This research discusses the analysis of speech acts in Abu Ubaidah's speech 36 days after the conflict between Hamas and Israel. The purpose of this research is to identify and analyze the types of illocutionary speech acts used in the speech based on John Searle's speech act theory. This research is important because it provides an in-depth understanding of how language is used in the context of conflict to achieve various communicative goals, as well as being a reference for the pragmatic linguistic study of John Searle's speech act theory as a language capable of producing action and providing additional information about the development of the Hamas-Israel conflict. The method used in this research is qualitative with library study techniques, allowing in-depth analysis of the speech material. The main findings of this research show that Abu Ubaidah's speech contains four types of illocutionary speech acts, namely assertive, directive, commissive and expressive. Examples of assertive speech acts include conveying information about war situations, while directive speech acts include praying and giving advice. Promises or oaths represent commissive speech acts, and expressive speech acts include greeting, criticizing, and praising. These results indicate that the speech was designed to not only convey information but also to motivate, inspire, and mobilize listeners. This research emphasizes the urgency of understanding language use in conflict contexts.